Endoscopic-Assisted Facelifting - Quatela, Vito C.; Azzi, Jean-Paul; Antunes, Marcelo B. (Facial Plastic Surgery, 2014)
Over the past two decades the use of endoscopes for facial rejuvenation gained wide popularity due to its reliable and reproducible results and limitation of the morbidity related to the open approaches. A thorough knowledge of the anatomy is of paramount importance to safely release all the fascial attachments while avoiding injuries to the facial nerve. The authors find the endoscopic forehead midface lift to be a reliable and safe procedure for facial rejuvenation.
Keywords: brow lift; midface lift; endoscopic; facelift